A trust management model based on mutual trust and a reward‐with‐punishment mechanism for cloud environments. (18th March 2021) - Guo, Liangmin; Yang, Hao; Luan, Kaixuan; Luo, Yonglong; Sun, Liping; Zheng, Xiaoyao
Abstract: Aiming at overcoming problems such as malicious entities and trust crises in cloud environments, a trust management model based on mutual trust and a reward‐with‐punishment mechanism is proposed in this paper. First, according to reputation values of entities and trust relationships among entities, we calculate the comprehensive trust values of a service request user to several candidate service providers and probe these providers with high comprehensive trust values. Second, we select a trade provider according to mutual trust. Finally, after the trade, we update the reputation values and other data of the request user, trade provider, and recommenders based on the final trade result to reward or punish them to various degrees, thus ultimately reducing malicious or dishonest behavior. The experimental results show that our model can effectively identify malicious entities to increase the trade success rate.